Experimental Results on Charge Fluctuations in Heavy-Ion Collisions. (17th January 2017) - Mishra, D. K.; Garg, P.; Netrakanti, P. K.; Pant, L. M.; Mohanty, A. K.
Abstract : We present a subset of experimental results on charge fluctuation from the heavy-ion collisions to search for phase transition and location of critical point in the QCD phase diagram. Measurements from the heavy-ion experiments at the SPS and RHIC energies observe that total charge fluctuations increase from central to peripheral collisions. The net-charge fluctuations in terms of dynamical fluctuation measure ν ( + -, d y n ) are studied as a function of collision energy (s N N ) and centrality of the collisions. The product of ν ( + -, d y n ) and 〈 N c h 〉 shows a monotonic decrease with collision energies, which indicates that at LHC energy the fluctuations have their origin in the QGP phase. The fluctuations in terms of higher moments of net-proton, net-electric charge, and net-kaon have been measured for various s N N . Deviations are observed in both S σ and κ σ 2 for net-proton multiplicity distributions from the Skellam and hadron resonance gas model for s N N < 39 GeV. Higher moment results of the net-electric charge and net-kaon do not observe any significant nonmonotonic behavior as a function of collision energy. We also discuss the extraction of the freeze-out parameters using particle ratios and experimentally measured higher moments of net-charge fluctuations. The extracted freeze-out parameters from experimentally measured moments and lattice calculations are found to be in agreement with the results obtained from the fit of particle ratios to the thermal model calculations.